Correlation Between Left Atrial Indices and Left Ventricular Diastolic Function Among Hypertensive Patients - Henry, Aiwuyo Osarume; John, Osarenkhoe Osaretin; Ejiroghene, Umuerri Ejiroghene; Fredrick, Aigbe Fredrick; Mike, Atoe-Imagbe Osagioduwa; Aisosa, Ogbomo Aisosa; Unuwaje, Okoke Eseoghene; Endurance, Evbayekha O.; Austine, Obasohan Austine (International Journal of Health Sciences, 2023)
Purpose: To compare LA indices and cardiac indices among hypertensive with left ventricular diastolic dysfunction Methodology: It is an echocardiographic based descriptive cross-sectional study. A total of 200 hypertensive patients were recruited from the cardiology clinics using systematic sampling method. Results: The mean age of the study population was 58.7 ±13.96 (58.42±13.29 for Hypertensives) years while the median age was 59years.The female to male ratio was 1:6. Majority of the cases had isolated diastolic dysfunction n=149 (74.5%), thirty-six (18%) had normal diastolic and systolic functions while 7.5% had combined systolic and diastolic dysfunction (n=15). Left atrial maximum volume correlated significantly with E/E Prime (P= 0.003) and E/A Ratio (P= 0.003). While Left atrial pre-A wave volume (P=0.025), Left atrial diameter did not correlate with IVRT, E/E', E/A ratio. Unique Contribution to Theory, Policy and Practice: Among the hypertensive patients E/E' significantly correlated positively with all phasic LA volumes compared to E/A ratio. LV mass independently predicted all LA phasic volumes.